P62 A rare case of chancroid in the UK. (16th June 2022) - Hazel, Caroline; Forsyth, Sophie; Daniel, Jessica
Abstract : Introduction: Chancroid, an ulcerating sexually transmitted infection of the genitals caused by Haemophilus ducreyi, is a rare presentation in the UK. We present a new case identified recently in the South West of England. Methods: A 26-year-old heterosexual male presented reporting a 2-3 week history of sores to his penis and a swelling in his left groin. A Sierra Leone national, the patient had recently returned to the UK following a six-month stay in the country. He disclosed one regular female sexual partner of 6 months, also from Sierra Leone. Examination of the groin revealed a tender, tense, erythematous mass extending approximately 5-6cm in length, 2cm in width, along the left groin crease. On examination of the penis, three irregularly shaped, wet, and deep-appearing ulcers were present at the coronal sulcus. 7 days later NAAT swabs for H.ducreyi returned a positive result. Results: The patient returned to clinic for treatment and review following the positive swab. Whilst the ulcers had not changed, the groin buboe had increased in size and discomfort, and had made mobilising difficult. Culture swabs were taken and he was treated with azithromycin 1g PO STAT as per BASHH guidance. At telephone review five days later he reported near complete resolution of symptoms. Discussion: Although a rare presentation, this case serves to highlight the need to consider a wide differential in patients presenting with genital ulceration not typical of HSV, especially in those whom have recently travelled outside the UK.